Burden of diabetes among various ethnic minorities in US and its implications - Mundra, Vishal (Journal of Social Health and Diabetes, 2014)
Introduction: Diabetes is one of the major healthcare issues worldwide. The average prevalence of diabetes was 11.7% in adults between 20-79 years of age in the US in 2011. This is a brief review of diabetes etio-pathogenesis and prevalence amongst various ethnic groups in the US. Materials and Methods: A pubmed search was done using key words diabetes, minorities and prevalence on September 15 2013. Relevant studies were selected for further review. In addition, more information was obtained from CDC websites. Discussion: As per CDC fact sheet 2011, 11.3% of all US adults ≥20 years of age had diabetes. 7.1% of non-Hispanic Whites, 8.4% of Asian Americans, 11.8% of Hispanics, and 12.6% of African-Americans (non-Hispanic Blacks) had diabetes in adults ≥20 years of age. Overall, 26.9% of adults of ≥65 years of age had diabetes in 2010. Amongst Native Indians, the prevalence ranges from 5.5% in Alaska natives to 33.5% amongst natives in Arizona. For immigrant south Asian population to the US (India, Pakistan, Nepal, Bangladesh and Sri Lanka), the prevalence has been documented to be varying from 17% to 29%. The wide variation in prevalence of diabetes poses a tough challenge to confine the epidemic as the measures have to be tailored to the needs of different race and ethnic groups. Conclusion: As these ethnic groups continue to grow, management of diabetes in these minorities confers a major health issue in the US.
Keywords: Diabetes; ethnic minorities; prevalence; social factors and implications